Impelemntasi Ice Breaking dalam Meningkatkan Motivasi Belajar PAI Siswa di SMP IT Tebuireng 4 Al-Ishlah Kuala Gading - Afni Dewitayanti; Nurwahid Ihsanudin (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The purpose of this study was to determine the effect of ice breaking in increasing students' learning motivation in Islamic Religious Education Subjects at SMP IT Tebuireng 4 Al-Ishlah Kuala Gading, Batang Cenaku District, Indragiri Hulu Regency. The research approach used was a quantitative approach with an experimental research type. The population in this study were all 30 seventh grade students. Research data were collected using three techniques, namely observation, questionnaires, and documentation. The results showed that before the implementation of ice breaking, students' learning motivation was relatively low, with an average pretest score of the experimental class of 57.07. After being given ice breaking treatment, learning motivation increased with an average posttest score of 65.93. The results of the t-test showed that t count > t table (4.052 > 1.701) and the Sig. value of 0.000 < 0.05, so that H₀ was rejected and Hₐ was accepted. Thus, this study concludes that ice breaking has a significant effect in increasing students' learning motivation in Islamic Religious Education subjects at SMP IT Tebuireng 4 Al-Ishlah Kuala Gading.